Structure and plasmonic properties of thin PMMA layers with ion‐synthesized Ag nanoparticles. Issue 9 (3rd February 2015) - Popok, Vladimir N.; Hanif, Muhammad; Mackova, Anna; Mikšovå, Romana
ABSTRACT: Silver nanoparticles are synthesized in polymethylmethacrylate by 30 keV Ag + ion implantation with high fluences. The implantation is accompanied by structural and compositional evolution of the polymer as well as sputtering. The latter causes towering of the shallow nucleated Ag nanoparticles above the surface. The synthesized nanoparticles can be split into two groups: (i) located at the surface and (ii) fully embedded in the shallow layer. These two groups provide corresponding spectral bands related to localized surface plasmon resonance. The bands demonstrate considerable intensity making the synthesized composites promising for plasmonic applications. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2015, 53, 664–672 Abstract : Silver nanoparticles are synthesized in polymethylmethacrylate by low‐energy implantation of silver ions. Sputtering, which accompanies the implantation, causes towering of the shallow nucleated silver nanoparticles above the surface. Therefore, the synthesized nanoparticles can be grouped into those located at the surface and fully embedded in the polymer. These two groups provide separated spectral bands related to localized surface plasmon resonance. The synthesized composites are promising for plasmonic applications.